2011
DOI: 10.4269/ajtmh.2011.09-0171
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Disturbances in Visceral Leishmaniasis (Kala-Azar)

Abstract: This study presents a cross-sectional analysis of the hormonal alterations of patients with visceral leishmaniasis. The diagnosis was established by the bone marrow aspiration and polymerase chain reaction test. Primary adrenal insufficiency was observed in 45.8% of patients; low aldosterone/renin plasma ratio in 69.4%; low daily urinary aldosterone excretion in 61.1%; and low transtubular potassium gradient in 68.0%. All patients had normal plasma antidiuretic hormone (ADH) concentrations, hyponatremia, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…Diagnosis and treatment of VL in renal transplant patients are also important because the course of VL can be complicated by variable degrees of graft dysfunction (17, 18, 33, 40–43). Acute leishmanial nephritis has been reported in the renal allograft of a Swiss patient 3 months after a well‐conducted treatment with L‐AmB (17).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Diagnosis and treatment of VL in renal transplant patients are also important because the course of VL can be complicated by variable degrees of graft dysfunction (17, 18, 33, 40–43). Acute leishmanial nephritis has been reported in the renal allograft of a Swiss patient 3 months after a well‐conducted treatment with L‐AmB (17).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…They concluded that renal dysfunction could be an important feature of kala-azar and might be associated with increased morbidity and mortality. More recently, Agenor et al [ 5 ] reported proximal tubular damage in a cross-sectional study of 55 patients with visceral leishmaniasis. Increased albumin excretion was observed in 44% of patients, accounting for 17% of the total urinary protein excretion.…”
Section: Renal Disease In Leishmaniasismentioning
confidence: 99%
“…Visceral Leishmaniasis (VL), also known as kala-azar, is a zoonosis caused by protozoan parasites from the genus Leishmania , which are typically found in tropical areas. The disease is endemic in many countries, including Brazil, which responds for 90% of cases in the Americas [ 1 ]. Due to its high incidence and the potential harms caused by the illness, it has become one of the World Health Organization’s (WHO) top priorities among neglected tropical diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%